PSYCHOLOGY OF DEVELOPING CREATIVE THINKING IN PRESCHOOL – AGE CHILDREN - Oripova Munisa (Bright Mind Publishing, 2025)
The article examines the psychology of developing creative thinking in preschool children. It highlights the importance of creative thinking, the teacher’s role in fostering it, and modern methods and interactive approaches. The significance of cooperation between family and preschool educational institutions in developing children’s creative potential is also discussed.
Keywords: Creative thinking, preschool education, child development, teacher, interactive methods, family cooperation.